Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
A (-1,7) B(1,3)
AB= y2-y1 / x2 - x1
= 3 - 7/ -1 -1
= -4/ -2
= 2x
Y= mx + c
3= 2(1) + c
3=2 + c
3-2=c
1=c
Equation of line = y= 2x + 1
AB= y2-y1 / x2 - x1
= 3 - 7/ -1 -1
= -4/ -2
= 2x
Y= mx + c
3= 2(1) + c
3=2 + c
3-2=c
1=c
Equation of line = y= 2x + 1
Answer:
-2
Step-by-step explanation:
Formula
([tex]y^{2}[/tex]-[tex]y^{1}[/tex]) ÷ ([tex]x^{2} - x^{1}[/tex])
So, (3 - 7) / (1 - (-1)) = -4/2
-4/2 = -2/1 = -2
I really hope this helps
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.